Numerical and experimental investigation of the cave passage model - Belov, Igor; Vabischevich, Maksim; Dedov, Oleg (Technology audit and production reserves, 2019)
The object of research is the soil model of the cave site, which approximates part of the underground structure of the Kyiv Pechersk Lavra (Kyiv, Ukraine). Long-term operation of underground historical buildings in cramped conditions at 100% humidity and under the influence of aggressive influences of internal and external factors leads to the exhaustion of their structural reliability. When restoring historical objects, it is advisable to combine the residual resources together with local structural reinforcements. Thanks to this concept, the original state is restored, and the structures can still perform their functions for a long time in the existing environment. Such amplifications create strong and rigid cells that combine the object into a single whole. This approach was tested by full-scale testing of a model of a fragment of the underground passage of the Far Caves, made of sandy loam in full size. The studies were carried out on the basis of the Test Center for Building Structures of the Kyiv National University of Construction and Architecture from 2012 to 2019. A technique for strengthening the soil mass with internal basalt reinforcement – flat frames – was developed. It was used in the restoration of certain sections of the underground structures of the Kyiv Pechersk Lavra. At the same time, numerous studies of the corresponding mathematical model were carried out with full-scale tests. A numerical-experimental approach to the analysis of the stress-strain state (SSS) of an underground structure model allows one to correctly determine the design parameters that will allow as close as possible to approximate a real underground structure. To increase the efficiency of using basalt reinforcement, the method of introducing individual rods into the damaged soil layer, which is under load, is investigated. Thus, it is proposed to use the reinforcements during the restoration of Variazhski caves of the Kyiv Pechersk Lavra, which received numerous damages in the form of vertical and inclined cracks in the ceiling and walls with soil outcrops.